Pemanfaatan Media pada Pembelajaran Pendidikan Agama Katolik Tingkat Sekolah Dasar di Wilayah Kota Pontianak - Suko; Thomas Kuslin; Martinus Marthin (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2021)
There is an assumption that the use of learning tools by Catholic Religion teachers is still uncommon, albeit essential. This paper intends to find and describe the utilization of media during this time by primary School of Catholic religious Education teachers in the city of Pontianak and at the same time finding the supporting factors and barriers in using the learning tools. The method used is qualitative with data collected from seven primary school Catholic religious teachers. Data is derived from live observation, interviews, and field documentation. Results are processed with qualitative data analysis techniques. The research team found that Catholic religious education teachers might not have maximized the utilization of the media in the Catholic religious learning process at school. Albeit the access to some supporting factors in some schools, such as: classrooms, computers, whiteboards, imageries, and teaching books, several factors reduced the usage of learning tools in Catholic Religion. Some of the internal factors were the teachers’ lack of ability in designing the media, or in using technologies necessary for that, or just the reluctance to learn them. As for the external factors, some schools did not have a particular room for Catholic religion classes. Hence, class alterations were common.